2D-LC–MS/MS to measure cleaved high-molecular-weight kininogen in human plasma as a biomarker for C1-INH-HAE. (October 2017) - Zhang, Guodong; Sexton, Daniel J; Faucette, Ryan R; Qiu, Yongchang; Wu, Jiang
Aim: C1-INH-HAE is caused by activation of plasma kallikrein which subsequently cleaves high-molecular-weight kininogen (HMWK) to generate bradykinin and cHMWK.Materials & methods: A novel ion-pair 2D LC–MS/MS assay was developed to measure the 46 kDa cHMWK in plasma as a biomarker for C1-INH-HAE. The sample preparation included sodium dodecyl sulfate denaturation, methanol crash, chymotryptic digestion and peptide enrichment by solid phase extraction.Results: The LLOQ was 200 ng/ml. The overall cHMWK recovery combining crash and digestion was 57.5%. The precision of the method was ≤12.7% and accuracy ≤-13.8%.Conclusion: A reagent-free LC–MS assay has been developed for the quantitation of 46 kDa cHMWK, which was shown to be elevated in plasma of C1-INH-HAE patients due to C1-INH deficiency relative to that of healthy subjects.